2024
DOI: 10.1021/acs.est.3c09600
|View full text |Cite
|
Sign up to set email alerts
|

Clothing Textiles as Carriers of Biological Ice Nucleation Active Particles

Christy J. Teska,
Markus Dieser,
Christine M. Foreman

Abstract: Microplastics have littered the globe, with synthetic fibers being the largest source of atmospheric microplastics. Many atmospheric particles can act as ice nucleators, thereby affecting the microphysical and radiative properties of clouds and, hence, the radiative balance of the Earth. The present study focused on the icenucleating ability of fibers from clothing textiles (CTs), which are commonly shed from the normal wear of apparel items. Results from immersion ice nucleation experiments showed that CTs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 84 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Additionally, a study by Teska et al looked at the ice nucleating activity of fibers from worn clothing textiles and found that polyester (PET) fibers had an increase in median freezing temperature, ΔT50, of 5.0°C compared with background freezing. 37 However, this high freezing activity was attributed to non-bacterial biological ice nucleating particles, as freezing dropped to around background freezing temperatures following H2O2 digestion, which deactivates any biological ice nucleating particles. This result stands in comparison to our pristine PET fragments which had a ΔT50 of 8.8 ± 1.1°C and 5.0 ± 1.1°C compared with background freezing at 1 wt % and 0.1 wt % concentrations compared with background freezing, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a study by Teska et al looked at the ice nucleating activity of fibers from worn clothing textiles and found that polyester (PET) fibers had an increase in median freezing temperature, ΔT50, of 5.0°C compared with background freezing. 37 However, this high freezing activity was attributed to non-bacterial biological ice nucleating particles, as freezing dropped to around background freezing temperatures following H2O2 digestion, which deactivates any biological ice nucleating particles. This result stands in comparison to our pristine PET fragments which had a ΔT50 of 8.8 ± 1.1°C and 5.0 ± 1.1°C compared with background freezing at 1 wt % and 0.1 wt % concentrations compared with background freezing, respectively.…”
Section: Resultsmentioning
confidence: 99%